Formation of the architectural space of health care facilities based on landscape design - Bulakh , Iryna (Transfer of innovative technologies, 2021)
Architecture is gradually changing along with the development of society, its changing perceptions of beauty, strength, usefulness, as well as the growing need for comfort, aesthetics, the ideal environment. For a long time, the architecture of health care facilities was perceived and, accordingly, mechanically designed exclusively as a kind of technically necessary shell to ensure the treatment of the impersonal mass of the population. This approach was due to the acute and rapid need for a quantitative supply of medical institutions to a large number of people in large areas. This is what happened in the last century in the post-Soviet countries - standard projects of medical institutions were "cloned" everywhere, which were integrated into the urban environment by huge industrial-panel arrays without regional, cultural and aesthetic connection with "genius loci" and urban context. Do we have the right to condemn this large-scale approach that prevailed in the twentieth century? No. At one time, he made it possible to resolve the important issues of providing medical care to the majority of the population of the Soviet Union. Thanks to the massive and economic industrial design and construction approach, Ukraine has received an extensive urban network of various health care facilities, which continue to perform their functions, accepting the harsh challenges and trials of global pandemics and epidemics. The main problem is that with the acquisition of sovereignty in Ukraine began protracted political-oligarchic clan "internecine wars", which for decades froze attention to improving, modernizing, updating and developing the architecture of health care facilities. A significant part of Ukrainian hospitals is in a condition that not only does not meet sanitary and other requirements, but even threatens the health and lives of patients and staff. But it is not customary to talk about it. The Soviet mentality, enshrined in our subconscious, forces everyone in their place to report on the order, on compliance, on the implementation of plans. Despite the long-standing disregard for the problems and issues of compliance of domestic medical architecture with world standards, the powerful and once the world's best "machine" continued to perform its functions, inertially moving down from its pedestal. But today, in 2021, we are frantically approaching the foot of the new "rock", which embodies all the latest advances in health care and which the world's leading countries have gradually, step by step, overcome with long-term state plan for the development of medicine and with periodic reforms in the medical field.